Big Data in Context Legal, Social and Technological Insights - Hoeren, Thomas; Kolany-Raiser, Barbara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is open access under a CC BY 4.0 license.
Keywords: Law; Big data; Data mining; Computers; Law and legislation; Mass media; International law; Intellectual property -- Law and legislation; Law; International IT and Media Law, Intellectual Property Law; Big Data/Analytics.; Data Mining and Knowledge Discovery; European Law; Media Law; Legal Aspects of Computing